Modulating immunogenic properties of HIV-1 gp41 membrane-proximal external region by destabilizing six-helix bundle structure - Banerjee, Saikat (Virology, 2016)
The C-terminal alpha-helix of gp41 membrane-proximal external region (MPER; (671)NWFDITNWLWYIK(683)) encompassing 4E10/10E8 epitopes is an attractive target for HIV-1 vaccine development. We previously reported that gp41-HR1-54Q, a trimeric protein comprised of the MPER in the context of a stable six-helix bundle (6HB), induced strong immune responses against the helix, but antibodies were directed primarily against the non-neutralizing face of the helix. To better target 4E10/10E8 epitopes, we generated four putative fusion intermediates by introducing double point mutations or deletions in the heptad repeat region 1 (HR1) that destabilize 6HB in varying degrees. One variant, HR1-Δ10-54K, elicited antibodies in rabbits that targeted W672, I675 and L679, which are critical for 4E10/10E8 recognition. Overall, the results demonstrated that altering structural parameters of 6HB can influence immunogenic properties of the MPER and antibody targeting. Further exploration of this strategy could allow development of immunogens that could lead to induction of 4E10/10E8-like antibodies.